Adaptive Reliable Multipath Provisioning in Survivable WDM Mesh Networks - Huang, Sheng; Martel, Chip; Mukherjee, Biswanath (Journal of optical communications and networking, 2010)
We investigate the problem of adaptive reliable multipath provisioning in next-generation backbone mesh networks employing optical wavelength-division multiplexing (WDM) and channelization techniques such as synchronous optical network/synchronous digital hierarchy (SONET/SDH) and supporting virtual concatenation (VCAT). VCAT enables multipath provisioning, but also introduces differential delay at destination nodes. How to guarantee service availability, using multipath provisioning, and meet the differential-delay constraint (DDC) is an important problem. We introduce the notation M:N(m) for multipath provisioning where a service path for a connection is set up with M primary paths and N backup paths, where each path has a fraction of the bandwidth of the connection, and (m) in this notation denotes "multipath.Ã¢â¬ With M:N(m) provisioning schemes, we develop an analytical model to analyze the end-to-end connection availability for the full bandwidth request. We propose two types of bandwidth migration methods, which can be implemented by a link-capacity adjustment scheme (LCAS) protocol of next-generation SONET/SDH, to optimize resource usage. Based on the M:N(m) analytical model, we develop an adaptive heuristic algorithm to provision a connection subject to the DDC while satisfying its service-level agreement (SLA). We show that, for end-to-end connection-availability-guaranteed service, multipath provisioning can achieve much better network performance than traditional single-path provisioning. With bandwidth migration, we can further improve multipath provisioning performance.